MANAJEMEN ADMINISTRASI DAN ORGANISASI - Ramlan, Ramlan; Elis Halimah, Elis Halimah; Cepi Hidayat, Cepi Hidayat; Hanafiah, Hanafiah; Muchtarom, Muchtarom (PT. Solusi Komunikasi Terapan, 2024)
Administrative and organizational management has a central role in the management of entities, including companies, government organizations, and non-profit institutions. The focus involves planning, organizing, implementing, and monitoring administrative activities to achieve goals efficiently. This research explores various aspects related to administrative and organizational management, with an emphasis on in-depth understanding of challenges and innovation in approaches to solving them. This research also identifies novelties in holistic approaches to administrative and organizational management, enriching management literature and practice. Through mixed-methods, this research combines qualitative and quantitative elements to provide a comprehensive picture of the factors that influence management, administration and organizations. In the discussion, this research highlights the urgency of organizational efficiency by considering factors such as vision and mission, organizational structure, strategy, human resources and organizational culture. Controlling is the key to building organizational efficiency by implementing appropriate management functions, economical use of resources, and sustainable organizational direction and dynamics. The conclusion of this research emphasizes that organizational efficiency and effectiveness are fundamental to achieving goals. Therefore, this research makes a new contribution to management literature and practice by detailing the factors that influence organizational efficiency and offering a new outlook on the management of modern organizations.